Description of the nymphs of Ectemnostega (Ectemnostegella) stridulata (Hungerford 1948) (Hemiptera: Heteroptera: Corixidae) - Konopko, Susana Amanda; Mazzucconi, Silvia Ana; Bachmann, Axel Oscar (Zootaxa, 2010)
The egg and the five nymphal instars of Ectemnostega (Ectemnostegella) stridulata are described and illustrated for the first time, with emphasis on the morphometry and chaetotaxy of selected structures. Comparison with the eggs of E. (Ectemnostegella) montana and E. (Ectemnostegella) peruana, and the nymphs of E. montana and E. (Ectemnostega) quadrata, are included. The egg of E. stridulata has a very short stalk like those of E. montana and E. peruana, and the three species differ in the chorionic structure. The nymphs of Ectemnostega share the presence of one dorsal abdominal scent gland on each of the segments IV–V. The number of spines on the profemur on the ventral and posteroventral surfaces distinguishes the nymphs of the subgenus Ectemnostega from the those of the subgenus Ectemnostegella. The nymphal characters most useful in identifying instars I–V of Ectemnostega are: the body length, the number of spines on the posteroventral surface of the mesofemur, setae on the posterodorsal surface and spines on the posteroventral surface of the mesotibia, setae on the posterodorsal surface of the mesotarsus, and the grade of development of the wing pads. The nymphal characters most useful in identifying species of Ectemnostega are: the number of spines on the posteroventral surface of the mesofemur, spines on the anterodorsal surface of the metatibia, and spines and swimming hairs on the anteroventral and posterodorsal surfaces of the metatarsus.